Developpe et reduis (encore)

V= 5 (t+3) + 2 (3t +4) - (5t - 3)
W= 6 (2x - 1) (3 - x)
X= (4x - 1) (3x + 5) - (x - 7)
Y= 3x + 5x(la lettre) (4 - 2x) - 2(x² - 3x + 5)
Z= 8+ 2x - 2x (3x - 4) + 5x(la lettre) (3-x)

merci d'avance

1

Réponses

2014-10-25T20:10:53+02:00
V= 5 (t+3) +2 (3t +4) - (5t -3)
  = 5 x t + 5 x 3 +2 x 3t +2 x 4 -5t +3
  = 5t +15 +6t +8 -5t +3
  = 6t +26

W= 6 (2x -1) (3 -x)
   = 6 x 2x - 6 x 1 +6 x 3 -6 x x
  = 12x -6 +18 -6x
  = 6x +12

X= (4x -1)(3x +5)- (x-7)
  = 4x x(fois)  3x +4x x(fois) 5 -1 x(fois) 3x -1 x 5 -x +7
  = 12x² +20x -3x -5 -x +7
  = 12x² +16x +2

Y= 3x +5x (4-2x) -2 (x² -3x +5)
  = 3x +5x x(fois) 4 -5x x(fois) 2x -2 x(fois) x² +2 x(fois) 3x -2 x 5
  = 3x +20x -10x² -2x² +6x -10
  = 29x -12x² -10

Z= 8 +2x -2x (3x-4) +5x (3-x)
  = 8 +2x -2x x(fois) 3x +2x x(fois) 4 +5x x(fois) 3 -5x x(fois) x(lettre)
  = 8 +2x -6x² +8x +15x -5x²
  = -11x² +8 +25x

J'espere qu'il n'y a pas de fautes :)
est ce que jai ds fautes?????
C'est tout bon merci beaucoup !! :o
de rien :)